2015
DOI: 10.1183/09031936.00014615
|View full text |Cite
|
Sign up to set email alerts
|

Smoke-free legislation and childhood hospitalisations for respiratory tract infections

Abstract: Second-hand smoke exposure is a major risk factor for respiratory tract infections (RTIs). Although evidence suggests important early-life health benefits of smoke-free public environments, the impact on childhood RTIs is unclear. We investigated the association between England's smoke-free legislation and childhood RTI hospitalisations.We used the Hospital Episode Statistics database to obtain nationwide data on hospital admissions for acute RTIs among children (<15 years of age) from 2001 to 2012. Hospitalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 36 publications
1
66
2
4
Order By: Relevance
“…These findings further stress the importance of protecting pregnant women and infants from passive smoke exposure, in both public and private areas. [22] Exposure to passive smoking in public places has been substantially regulated over the past decade with significant health gains for children [23,24]. While increased population awareness and the adoption of smoke free environments have been found to reduce exposure inside the house [25], further action is needed to reduce exposure in other private areas that have been identified to contribute significantly to overall passive smoke exposure during the gestational period, such as exposure within the family car [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings further stress the importance of protecting pregnant women and infants from passive smoke exposure, in both public and private areas. [22] Exposure to passive smoking in public places has been substantially regulated over the past decade with significant health gains for children [23,24]. While increased population awareness and the adoption of smoke free environments have been found to reduce exposure inside the house [25], further action is needed to reduce exposure in other private areas that have been identified to contribute significantly to overall passive smoke exposure during the gestational period, such as exposure within the family car [26].…”
Section: Discussionmentioning
confidence: 99%
“…The independent role of prenatal and postnatal exposure to active and passive smoking on the development of early wheeze in children Vardavas CI (1,2) , Hohmann C (3,4) , Patelarou E (1,5) , Martinez D (6,7,8) , Henderson AJ (9) , Granell R (9) , Sunyer J (6,7,8,10) , Torrent M (6,11) , Fantini MP (12) , Gori D (12) , AnnesiMaesano I (13,14) , Slama R (15) , Duijts L (16) , de Jongste JC (17) , Aurrekoetxea JJ (18,19,20) , Basterrechea M (7,19,20) , Morales E (6,7,21) , Ballester F (7,22) , Murcia M (7,22) , Thijs C (23) , Mommers M (23) , Kuehni CE (24) , Gaillard EA (25) , Tischer C (26) , Heinrich J (26,27,) , Pizzi C…”
mentioning
confidence: 99%
“…However, methodological limitations include the lack of a control group, (Mackay et al, 2010;Millett et al, 2013;Herman and Walsh, 2011;Rayens et al, 2008) not accounting for other tobacco control policies, (Mackay et al, 2010;Millett et al, 2013;Naiman et al, 2010;Herman and Walsh, 2011;Rayens et al, 2008) or not distinguishing state from local policies (Herman and Walsh, 2011;Shetty et al, 2011). More recent studies have found reductions in hospitalizations for children's respiratory tract infections, primarily attributed to decreases in lower respiratory infections, after the introduction of country-wide smoke-free legislation (Been et al, 2015;Lee et al, 2016). Despite plausible mechanisms, (US Department of Health and Human Services, 2006) we are not aware of any studies that have examined the effects of secondhand smoke exposure on children's hospital admissions or ED visits for ear infections.…”
Section: Introductionmentioning
confidence: 92%
“…In this issue, BEEN et al [1] present the first study on smoke-free law and hospitalisation for RTIs in children. They analysed hospital episode statistics to investigate the association between smoke-free legislation introduced in England on July 1, 2007, and hospitalisation trends for upper and lower RTIs from 2001 to 2012 in children <15 years of age.…”
mentioning
confidence: 99%
“…The claim by SCHROEDER AND WARNER [36] that "at a time when all eyes are focused on health care reform, escalating medical costs, and childhood obesity, cigarette smoking remains by far the most common cause of preventable death and disability," is still true and also applies to Europe. BEEN et al [1] give us even more evidence that child health can be improved easily, effectively and cheaply, if we want.…”
mentioning
confidence: 99%